Mendelian randomization analysis reveals causal factors behind diabetic nephropathy: evidence, opportunities, and challenges - Huang, Qinchuan; An, Chen; Tang, Shiyun; Leng, Yulin; Zhang, Yaowen; Wan, Bin; Han, Yutong; Luo, Yue; Xie, Chunguang (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DN), as the most serious minor vascular complication of diabetes, imposes a significant socioeconomic and medical cost around the world, and its prevention and treatment are a major challenge in the current medical community. Observational studies and randomized controlled trials have revealed protective and risk factors for some DN. However, the conclusions of these researches may be influenced by several types of confounding. Mendelian randomization is a new epidemiological method mainly used to infer the causal relationship between exposure and outcome. Many Mendelian randomization studies have found potential causal relationships between DN and some diseases and lifestyle habits, thus providing valuable data for future mechanistic studies as well as the development and implementation of clinical prevention strategies. As a result, the purpose of this review is to evaluate the published Mendelian randomization study of DN, using the bibliometric research method, analyze the current research status and hot spots, and further summarize the genetic evidence about the potential protection of DN and risk factors to provide new inspiration for the etiology of DN and as a reference for clinical intervention.